Educational Literacy Assistance and Training for Indonesian Migrant Children in Malaysia - Azizah, Siti Nur; Zahry, Ariel Alvi; Putri, Anika Rahma; Putri, Tiana Amalia; Fadhillah, Maya Putri; Arumsari, Putri Ayu; Purba, Nuraliya; Anoura, Farras (Buletin KKN Pendidikan, 2023)
Reading, writing, and counting are basic abilities that every student must have, especially at the elementary school level. Based on the results of initial observations and direct interviews with relevant community organizations, children have limited skills and abilities in reading, writing, and arithmetic due to certain conditions. This service is here to assist and train children of Indonesian migrant descent who live in Kuala Lumpur, Malaysia. This activity uses the foster sister method or approach, which includes reading, writing, and arithmetic assistance to improve the quality of human resources, especially in education. This educational literacy training can improve people's standard of living. Thus, children have access to knowledge in the fields of education, technology, and information. The results obtained from this activity were an increase in the reading, writing, and arithmetic abilities of children of WMI descent who live in Kuala Lumpur, Malaysia.